Incidence and risk factors of tuberculosis among the elderly population in China: a prospective cohort study - Jun Cheng; Yan-Ni Sun; Can-You Zhang; Yan-Ling Yu; Li-Hong Tang; Hong Peng; Ying Peng; Yu-Xia Yao; Shuang-Yi Hou; Jian-Wei Li; Jin-Ming Zhao; Lan Xia; et al. (BMC, 2020)
Abstract Background China is facing challenges of the shifting presentation of tuberculosis (TB) from younger to elderly due to an ageing population, longer life expectancy and reactivation disease. However, the burden of elderly TB and influence factors are not yet clear. To fill the gap, we generated a cohort study to measure the magnitude of TB incidence and associated factors among the elderly population aged 65 years and above in China. Methods In this cohort established in 2013 through a prevalence survey conducted in selected sites, a total of 34 076 elderlies without TB were enrolled into two-year follow-up. We used both active and passive case findings to find out all TB patients among them. The person-year (PY) incidence rates for both bacteriologically positive TB and active TB were calculated. Cox proportional regression model was performed to test effect of risk factors, and the population attributable fraction (PAF) of each risk factor contributing to incident TB among elderlies was calculated. Results Over the two-year follow-up period, a total of 215 incident active TB were identified, 62 of which were bacteriologically positive. The incidence rates for active TB and bacteriologically positive TB were 481.8 per 100 000 PY (95% CI: 417.4-546.2 per 100 000 PY) and 138.9 per 100 000 PY (95% CI: 104.4-173.5 per 100 000 PY), respectively. Incident cases detected by active case finding were significantly higher (P < 0.001). Male, non-Han nationality, previously treated TB, ex/current smoker and body mass index (BMI) < 18.5 presented as independent predictors for developing TB disease. For developing bacteriologically positive TB, the biggest contribution was from self-reported ex or current smoker (18.06%). And, for developing active TB, the biggest contribution was from non-Han nationality (35.40%), followed by male (26.80%) and age at 75 years and above (10.85%). Conclusions Ageing population in China had a high TB incidence rate and risk to develop TB disease, implying that National TB Program (NTP) needs to prioritize for elderly. Active case finding should be applied capture more active TB cases among this particular population, especially for male, non-Han nationality, and those with identified risk factors.